Analysis Effectiveness Execution Productionof Tea Bottle Sosro (Case Study: SinarSosro Malang) - Vita Kartika Widhianingtyas; Almukaromah Dewi Puspita; Liem Gai Sin (AIBPM Publisher, 2018)
The purpose of this study is to create or improve the use of goods or services for others. The process of production execution that can be directly done by the consumer one of them. Running the production process can be used directly and directly in producing goods or services that can be enjoyed by consumers. The objectives of production are to increase the value of use, increase the prosperity of the community, increase profits, increase business fields and maintain the business continuity of the company. This research uses PT SinarSosro as a case study. Data collection is done by interview and secondary data obtained from retail and to end user. The data were analyzed by qualitative descriptive technique, for guides to focus the research according to the facts in the field. Keywords: production management, PT SinarSosro, qualitative descriptive